Interdisciplinary Concepts in Cardiovascular Health Volume II: Secondary Risk Factors - Wakabayashi, Ichiro; Groschner, Klaus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book provides an introduction to the principles of both cardiovascular epidemiology and molecular pathophysiology; as a unique aspect, it also outlines and discusses the molecular concepts underlying epidemiological observations. This second volume is focused on all aspects concerning (3z(Bsecondary risk factors(3y (Bin terms of diseases associated with enhanced risk for cardiovascular events. The book promotes the use of interdisciplinary approaches in the field of preventive medicine based on recent advances in molecular and cellular pathophysiology. The book offers a valuable resource for researchers in basic biomedical fields and clinical scientists alike, as well as guidelines for novel avenues of research in both basic pathophysiology and cardiovascular therapy and preventions
Hypertension and vascular dysfunction -- Obesity and diabetes -- Hyper- and dyslipoproteinemias -- Hyperuricemia -- Proteomics towards biomarkers discovery and risk assessment.
Keywords: Medicine; Metabolic diseases; Biomedicine; Molecular Medicine; Metabolic Diseases; Health Promotion and Disease Prevention